Analisis Rasio Keuangan Dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Manufaktur Di BEI - Taruh, Victorson (Jurnal Pelangi Ilmu, 2012)
This research wants to examine the effects of total asset turnover, currrent liabilities to inventories and gross profit margin to profit growth of manufacture company. The sampling technique used in this research is purposive sampling, with some criteria, those are: (1) the manufacture company listed in Indonesia Stock Exchange in research period and still operating consistencly in the research period; (2) the available of financial statement as the research period; (3) the manufacture company has not negative profit. The result of this study that data has fulfill the classical asumption, such as: no multicolinearity, no autocorrelation, no heteroscedasticity and distributed normally. from the results of the regression analysis indicates that the variabel on a partial profit significant affect against profit growth total asset turnover and current liabilities to Inventories have no affect significant against profit growth. Predictive ability of thitd variabel simultaneously 5,5%.